Pembelajaran Online dalam Perspektif Teori Behavioristik - Akbar Nur Aziz; Azam Syukur Rahmatullah; Anisa Dwi Makrufi; Muhammad Samsudin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The purpose of this paper is to provide a view of behavioristic learning theory on the online learning process during the COVID-19 pandemic and the implications of behaviorist learning theory on the online learning process. The method used is a literature review with a descriptive qualitative approach. Sources of data obtained from books and journals through a search on Google Scholar. The results of this study indicate that the application of behaviorist theory in online learning is to shape student behavior in a non-face-to-face manner by providing stimulus and student reactions seen from changes in behavior. Even though it is carried out through a screen, the teacher can make habits that contain elements of skills in the learning process. There are advantages of behavioristic theory in online learning, namely teachers become observant of classroom conditions and situations, shape student behavior according to expectations, can replace stimuli if they are not suitable, and are suitable for use on students who are happy with practical lessons. In addition, behavioristic theory also has shortcomings in online learning, namely the teacher s lack of understanding of technology and inadequate internet access and online learning facilities. In addition, the drawback of behavioristic theory is that it makes students passive, and this theory does not see differences in the level of understanding of students even though they have the same ability due to the intelligence factor of students.